PENINGKATAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI (KARYAWAN) MELALUI PELATIHAN PENGISIAN SPT TAHUNAN PAJAK PENGHASILAN ORANG PRIBADI - Muhammad Hasyim Ashari (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
This community service activity aims to train employees who have more than one position from different business entities in one business group located in Lawang, Malang, East Java, regarding calculating and reporting the Annual Tax Return of Personal Income. The method used in this activity is training in calculating and reporting the Annual Tax Return of Personal Income who have positions in three business entities in the same business group. Based on the results of community service, it is concluded that employees who have a personal income tax (PPh 21) can calculate the tax payable. The combined income will be underpaid on the Annual Personal Income Tax because they have income from two or more employers (business entities) in one business group. So you must make an Electronic Deposit Letter via e-billing first before reporting the Annual Tax Return electronically via e-filling or e-form.